PENGEMBANGAN MODUL PEMBELAJARAN PADA MATA PELAJARAN NC/CNC KELAS XI DI SMK NEGERI 1 SUMATERA BARAT - Hendrik Swandi; Nelvi Erizon; Refdinal Refdinal; Yufrizal A (Unversitas Negeri Padang, 2020)
The learning media developed is a learning module that is able to enable students to learn independently. This study aims to develop a learning module and determine the validity of the module and the practicality of the module being developed. In the development of the learning module using the type of R&D (Research and Development) research which refers to the 4D development model (define, design, develop, and disseminate). This research was conducted in the academic year 2020/2021 in odd semester. In the development of the TU 2A CNC learning module, it goes through several 4 D development stages, the first stage is the define stage, the two stages of design (design), the three stages of develop (development), and the last stage of disseminate (deployment). The types of data in this research are quantitative and qualitative using instruments in the form of a questionnaire, which at the development stage is carried out by validity tests and practicality tests where the validity test is tested on 2 mechanical engineering education lecturers as material experts and media experts, while in the practicality test it is tested on 1 subject teacher and 30 responses from mechanical engineering students at SMKN 1 West Sumatra. The results of the test show that the TU 2A CNC machine engineering learning module is very suitable for use as a learning medium.